Cinemática e desempenho muscular do tronco e a atividade de sentado para de pé em indivíduos pós-acidente vascular encefálico e saudáveis - Paula Fernanda de Sousa Silva (2014)
Subjects with stroke commonly present trunk structures and functions impairments, as well as limitations for sit-to-stand (STS) movement. In healthy subjects, the biomechanics of this activity is commonly characterized by variables related to trunk kinematics and to trunk muscle performance. However, in subjects with stroke, the investigation of these variables and their relation with the STS performance have not been adequately clarified. In this context, the purposes of the present study were: a) to compare STS performance, kinematic variables and trunk muscle performance between subjects with stroke and matched healthy subjects; and b) to investigate if there is a relationship between STS movement and the kinematic variables and trunk muscle performance in these subjects. Eighteen subjects in the chronic phase of stroke (13 men and five women, 59.78 ± 2.34 years of age), and 18 healthy matching subjects regarding age, gender, body mass index, and physical activity levels were assessed. The measurements used to assess the STS performance were: five-repetition sit-to-stand test (clinical measurement) and total duration of the STS as well as of Phases I and II of the STS, at self-selected and fast speeds (laboratory measurement, motion analysis system). The kinematic variables of the trunk, during the STS, were also obtained (motion analysis system): maximum forward flexion, peak of the flexion momentum and instant of the STS in which this occurred. The muscle performance of flexors/extensors of the trunk was clinically characterized in the laboratory by the peak torque and total work normalized by the trunk mass variables (isokinetic dynamometer, range of motion of 65º of flexion-extension of the trunk; three series of three repetitions at 60º/s). To compare groups, the students independent samples T-test was used. In order to investigate the correlations in the total sample (n=36), the Pearson Correlation Coefficient was used (=0,05). Compared to the matched healthy subjects, the subjects with stroke showed, predominantly, worse clinical (p<0.001) and laboratory (p0.022) performance in the STS, lower peak flexor momentum of the trunk (p<0.001), and lower values in all variables of muscular performance (p0.001). Predominantly, significant correlations were verified between the clinical and laboratorial performance in the STS, with the maximum trunk forward flexion (0.001p0.028;0.37r0.54), peak trunk flexor momentum (p0.001;0.58r0.71), peak torque and total work normalized by the trunk mass of the trunks flexors/extensors (p0.022; 0.39r0.63). Therefore, subjects present a worse STS performance and worse biomechanical characteristics and trunk muscle performance, when compared to matched healthy subjects. These variables present significant correlations to each other, indicating that such worse STS performance might be related to the difficulties that subjects with stroke have to generate/transfer the flexor momentum, as well as their worse trunk muscle performance. Evaluations/interventions meant to improve the performance of these subjects in the STS must consider the trunk structures and functions.